Testing the Validity of Gibrats Law in the Context of Profitability and Leverage - Yakubu, Ibrahim Nandom (The Economics and Finance Letters, 2020)
This study seeks to test the validity of Gibrat’s Law of Proportionate Effect for listed firms in Ghana over the period 2008-2017. The study also investigates whether firms’ profitability and leverage affect the validity of Gibrat’s Law. Employing the fixed effects regression technique, the results show that Gibrat’s Law does not hold for all firms when the effect of firm size on growth is directly examined. In the presence of profitability, Gibrat’s Law is valid for both financial and non-financial firms. The findings further observe that, while Gibrat’s Law holds for non-financial firms in the presence of leverage, it is rejected for financial firms. Given the direct and significant impact of size on firm growth, the study concludes that Gibrat’s proposition that the growth rate of a given firm is independent of its size does not hold for listed firms in Ghana. The study discusses relevant recommendations based on the findings.